Solidification of ionic liquid redox electrolytes using agarose biopolymer for highly performing dye-sensitized solar cells. (10th October 2015) - Bidikoudi, Maria; Perganti, Dorothea; Karagianni, Chaido-Stefania; Falaras, Polycarpos
Abstract: Solvent free, ionic liquid based redox electrolytes were prepared and subsequently solidified using agarose natural polysaccharide. The electrolytes were thoroughly characterized, and their electrical properties were investigated, while they were incorporated in dye-sensitized solar cells (DSCs) that presented excellent efficiency (PCE = 3.98%), higher than the corresponding reference liquid electrolyte (PCE = 3.84%). At the same time, they compare well to DSCs using solid redox electrolytes based on the poly ethylene oxide, this comparison highlighting the device stability and great potential of the biopolymers as efficient solidifiers.